Pemanfaatan Pompa Air Sederhana Sebagai Alat Irigasi Asuhan Mandiri Tanaman Toga Di Desa Jimbaran Kulon, Sidoarjo - M. Andrian Daffa Affandi; Firmansyah, Mashuri; Utami, Veronica Nabilah; Taufiq, Zahra Febriana; Dutahatmaja, Angga (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to implement and evaluate the use of simple water pumps as an alternative irrigation tool to support the independent care program (ASMAN) of family medicinal plants (TOGA) in Jimbaran Kulon Village, Sidoarjo. Activities include identifying water sources, installing water pumps, technical training for the community, and monitoring and evaluating plant productivity. The results show that the use of simple water pumps can increase irrigation efficiency and TOGA harvest yields by up to 40%. Technical training has also succeeded in increasing community understanding and independence in operating and maintaining the tool. In addition to having a positive impact on agriculture, this technology is considered environmentally friendly, energy efficient, and has the potential to be developed as a model for empowering village communities. Therefore, the use of simple water pumps is an appropriate solution that supports the sustainability of TOGA cultivation while improving the welfare of local communities.